Musik Sebagai Sarana Pastoral Konseling Dalam Meningkatkan Kesehatan Mental Individu Melalui Terapi Integratif - Oba, Monica Erika Gracia (PT. Giat Konseling Nusantara, 2025)
This study explores the effectiveness of Music as a Pastoral Counseling Tool in improving individual mental health through integrative therapy. Using a qualitative approach and in-depth interview method, this study shows that Music as a Pastoral Counseling Tool can be an effective tool to improve individual mental health and help them cope better with life challenges. This study also shows that Music as a Pastoral Counseling Tool can help individuals increase spiritual awareness and understand the meaning and purpose of their lives.